Interpersonal violence against women and maternity care in Migori County, Kenya: evidence from a cross-sectional survey - Schellhammer, Sophie K.; Starnes, Joseph R.; Mudhune, Sandra; Goore, Lou; Marlar, Lauren; Oyugi, Samuel; Wamae, Jane; Shumba, Constance S.; Rogers, Ash; Mbeya, Julius; Vill, Beffy; Otieno, Angeline S.; et al. (Frontiers in Global Women's Health, 2024)
Interpersonal violence is a major public health concern, with 24% of Kenyan women reporting physical violence perpetrated by a current husband/partner. IPV impacts physical and mental health outcomes, particularly for pregnant women by increasing the risk of perinatal mortality, low birth weight, and preterm birth. This study aims to identify variables associated with IPV and assess the effects of IPV on prenatal and peripartum maternal healthcare in Migori. Responses to cross-sectional household surveys from female respondents aged 18 and older in 2021 were analyzed. Group-wise comparisons, logistic regression analyses were performed to describe community prevalence, factors associated with IPV against women, and the effect of IPV exposure on prenatal and peripartum health. This study finds that 2,306 (36.7%) of the 6,290 respondents had experienced lifetime IPV. IPV experience was associated with the age group 25-49 (adjusted odds (aOR) 1.208; 95%CI:[1.045-1.397]; p=0.011), monogamous marriage (aOR 2.152; 95%CI: [1.426-3.248]; p<0.001), polygamous marriage (aOR 2.924; 95%CI: [1.826-4.683]; p<0.001), being widowed/divorced/separated (aOR 1.745; 95%CI: [1.094-2.786]; p<0.001), feeling an attitude of "sometimes okay" toward wife beating (aOR 2.002 95%CI: [1.651, 2.428]; p<0.001), having been exposed to IPV in girlhood (aOR 2.525; 95%CI: [2.202-2.896]; p<0.001) and feeling safe in current relationship (aOR 0.722; 95%CI: [0.609, 0.855]; p<0.001). A depression score of mild (aOR 1.482; 95%CI: [1.269, 1.73]; p<0.001) and severe (aOR 2.403; 95%CI: [1.429, 4.039]; p=0.001) was also associated with IPV experience, and women who experienced emotional abuse were more likely to experience IPV (aOR 10.462; 95% CI: [9.037, 12.112]; p<0.001). Adjusted analyses showed that having experienced IPV was negatively associated with attending at least four antenatal care visits during the most recent pregnancy (OR 0.849, p=0.044) and with having a skilled birth attendant (OR 0.638, p=0.007). IPV is prevalent in Migori County, Kenya, more so among women aged 25-49, those residing in West Kanyamkago, those in a monogamous/polygamous marriage, those who have been widowed/divorced/separated, and those with severe depressive symptoms. Further, IPV exposure is associated with lower use of maternal care services and may lead to worse maternal health outcomes. There is need for addressing social and gender norms that perpetuate IPV, through policy interventions.